Magnetic domain walls interacting with dislocations in micromagnetic simulations - Sami Kaappa; Suvi Santa-aho; Mari Honkanen; Minnamari Vippola; Lasse Laurson (Communications Materials)
Abstract Defects, impurities, and embedded particles in ferromagnetic materials are long known to be responsible for the Barkhausen effect due to the jerky field-driven motion of domain walls and have more recently been shown to play a role also in domain wall dynamics in nanoscale ferromagnetic structures used in spintronics devices. Simulating the magnetic domain wall dynamics in the micromagnetic framework offers a straightforward route to study such systems and phenomena. However, the related work in the past suffers from material imperfections being introduced without proper physical foundation. Here, we implement dislocation stress fields in micromagnetic simulations through the induced anisotropy fields by inverse magnetostriction. The effects of individual dislocations on domain wall dynamics in thin films of different Fe surface lattice planes are characterized numerically. As a demonstration of the applicability of the implementation, we consider disorder fields due to randomly positioned dislocations with different densities, and study the avalanche-like transient approach towards the depinning transition of a domain wall driven by a slowly increasing external magnetic field.